Meliaceae cubanas: Taxonomía numérica - Albert Fuentes, Delhy (1995)
As a result of the revision of the Meliaceae family for the Flora of the Republic of Cuba, the affinity relationship among species and the more important characters for their diagnostic and adaptive value are discussed.